Shaping National Character in Early Grade Elementary School Students Through Social Sciences Learning in the Medeka Curriculum Era - Dela Lestari; Nazwa Kusumawicitra; Nurhalizah Apriyani; Tin Rustini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
By looking at the Merdeka curriculum in primary schools, this research investigates the role of social studies education in fostering Indonesian character in primary school students. This curriculum aims to provide students with a strong, genuine understanding and respect for Indonesian culture while adhering to the values derived from Pancasila, which is the identity of the Indonesian nation. Social studies education becomes important in order to foster the character of students, including the cultivation of moral values in themselves both in the home, school and community environment. The data collected in this study were collected through surveys and analyzed through the literature study method. Data were obtained from various sources, including academic journals, student documents, and relevant research topics. This research found that social studies education can improve students' understanding of the daily life that must be carried out by applying the nation's values in their daily lives. It can also help them learn academically and support them in interacting and collaborating to solve everyday problems, which helps them in making the right choices for their brighter future.